2021
DOI: 10.1021/acssynbio.1c00074
|View full text |Cite
|
Sign up to set email alerts
|

Microbially Guided Discovery and Biosynthesis of Biologically Active Natural Products

Abstract: The design of small molecules that inhibit disease-relevant proteins represents a longstanding challenge of medicinal chemistry. Here, we describe an approach for encoding this challenge-the inhibition of a human drug target-into a microbial host and using it to guide the discovery and biosynthesis of targeted, biologically active natural products. This approach identi ed two previously unknown terpenoid inhibitors of protein tyrosine phosphatase 1B (PTP1B), an elusive therapeutic target for the treatment of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 102 publications
2
31
1
Order By: Relevance
“…coli. We used a bacterial two-hybrid (B2H) system that links the inhibition of PTP1B to the expression of a gene for antibiotic resistance (Figure C) . In this system, Src kinase phosphorylates a substrate domain, allowing it to bind to an Src homology 2 (SH2) domain; the substrate–SH2 complex activates the transcription of a resistance gene by localizing RNA polymerase to its promoter.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…coli. We used a bacterial two-hybrid (B2H) system that links the inhibition of PTP1B to the expression of a gene for antibiotic resistance (Figure C) . In this system, Src kinase phosphorylates a substrate domain, allowing it to bind to an Src homology 2 (SH2) domain; the substrate–SH2 complex activates the transcription of a resistance gene by localizing RNA polymerase to its promoter.…”
Section: Resultsmentioning
confidence: 99%
“…PTP1B dephosphorylates the substrate domain, preventing transcription, and the inactivation of PTP1B re-enables it. In prior work, we used this system to identify terpene synthases that can generate inhibitors of PTP1B . In a prior screen, both amorphadiene synthase and α-bisabolene synthase conferred a significant survival advantage (i.e., growth on solid media with ∼800 μg/mL spectinomycina concentration sufficient to kill strains with inactive variants of both terpene synthases); subsequent biophysical analyses indicated that amorphadiene inhibits PTP1B by binding to an allosteric site (Figure B) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations